Pre-service teacher training in Malawi: findings of a pilot study on the viability of media players for teacher development - Carrier, Carol; Finholt-Daniel, Matt; Sales, Gregory C (International Journal of Education and Development using Information and Communication Technology, 2012)
As part of the United States Agency for International Development (USAID funded Malawi Teacher Professional Development Support project, a sub-task was the piloting of an alternative technology that could be used for improving the quality and consistency of teacher continued professional development (CPD). The pilot, which included 26 open and distance learning (ODL) student teachers, was launched in the spring of 2011 using a low-cost portable MP3 multi-purpose device. A short course on numeracy, containing 5 weekly lessons, was piloted. Each lesson consisted of one or two readings, two videos, and an assignment that directed the learner to complete tasks and document their completion using the camera and audio recorder features of the media player. The viability of using the media player for CPD was evaluated on the ease of use, effectiveness of instruction, and potential for long-term scalability. The evaluation results demonstrated that, with a small amount if initial training, the devices were easy to use and they effectively deliver instruction. Scalability, however, is critical to the long-term success of an initiative based on these or similar devices. An analysis suggests that an affordable option worth considering is the systematic, shared use of media player devices within schools. This approach could dramatically reduce the cost of using this alternative technology for ODL training to pennies per lesson. [PUBLICATION ABSTRACT]
Place: Bridgetown Publisher: University of the West Indies KerkoCite.ItemAlsoKnownAs: 2339240:H5SC64NG 2405685:HNDKMF9C 2534378:5F2RLGL3 2534378:783739U4
Keywords: Distance learning; Education; Learning; Malawi; Software; Student teachers; Teacher education; Teaching; __:import:01; __:match:final; __:matched; __:study_id:2096523; __finaldtb; ⛔ No DOI found